Intimate Partner Violence During a Public Health Crisis: Variations in Conflict and Post Conflict Contexts - Iesue, Laura (Crime & delinquency, 2024)
This study draws on survey data collected in a country embroiled in war, Ukraine, and a post-conflict country, Guatemala, to examine the influence of traumatic events on intimate partner violence victimization. Logistic regression models revealed that experiencing pandemic stress (e.g., fears of the virus, vaccine issues, and health care concerns) and daily hassles (e.g., family issues, financial problems, and prejudice) increased the risk of physical and verbal abuse victimization in both countries. Exposure to crises such as war and genocide predicted the risk of physical abuse victimization in Guatemala. The effects of pandemic stress in Ukraine and exposure to crises in Guatemala on victimization were more pronounced among those with fewer daily hassles. Variations among demographic groups were also observed.